The Politics of the Art in Britain - Gray, C. author. aut Link
XIII, 224 p.
Keywords: The organization and management of the arts and public-sector arts organizations in Britain have undergone major changes over the last twenty years. This book analyzes the process and politics of change in the world of the arts and develops an analytical framework for understanding an under-researched area of British political life.